Molecular Cloning and Characterization of a P-Glycoprotein from the Diamondback Moth, Plutella xylostella (Lepidoptera: Plutellidae) - Tian, Lixia (Molecular Diversity Preservation International (MDPI), 2013)
Macrocyclic lactones such as abamectin and ivermectin constitute an important class of broad-spectrum insecticides. Widespread resistance to synthetic insecticides, including abamectin and ivermectin, poses a serious threat to the management of diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), a major pest of cruciferous plants worldwide. P-glycoprotein (Pgp), a member of the ABC transporter superfamily, plays a crucial role in the removal of amphiphilic xenobiotics, suggesting a mechanism for drug resistance in target organisms. In this study, PxPgp1, a putative Pgp gene from P. xylostella, was cloned and characterized. The open reading frame (ORF) of PxPgp1 consists of 3774 nucleotides, which encodes a 1257-amino acid peptide. The deduced PxPgp1 protein possesses structural characteristics of a typical Pgp, and clusters within the insect ABCB1. PxPgp1 was expressed throughout all developmental stages, and showed the highest expression level in adult males. PxPgp1 was highly expressed in midgut, malpighian tubules and testes. Elevated expression of PxPgp1 was observed in P. xylostella strains after they were exposed to the abamectin treatment. In addition, the constitutive expressions of PxPgp1 were significantly higher in laboratory-selected and field-collected resistant strains in comparison to their susceptible counterpart.